Performance evaluation of a utility-scale dual-technology photovoltaic power plant at the Shagaya Renewable Energy Park in Kuwait. (November 2020) - AL-Rasheedi, Majed; Gueymard, Christian A.; Al-Khayat, Mohammad; Ismail, Alaa; Lee, Jared A.; Al-Duaj, Hamad
Abstract: This study presents the actual monitoring data and performance analysis results obtained from the 11.15-MW grid-connected Shagaya Photovoltaic Park, Kuwait (latitude 29.2°N, longitude 47.04°W). The plant was specifically built to compare two PV technologies: a Thin-Film (TF) installation of 5.5 MW and a Polycrystalline (PC) silicon installation of 5.6 MW. The plant has been designed as a pilot testbed to evaluate the performance of different grid-tied PV technologies under a hot desert environment. A 25-month monitoring period has provided important information that will be used to prepare the design of upcoming GW-size PV projects at Shagaya. Performance parameters of the PV system evaluated here include: final yield, reference yield, array yield, system losses, array capture losses, cell temperature losses, PV module efficiency, system efficiency, inverter efficiency, performance ratio, and capacity factor. Comparison between the TF and PC PV subsystems reveals no significant difference between the two technologies regarding annual reference yields (1805 kWh / kW for TF and 1810 kWh / kW for PC), performance ratios (80.0% for TF and 80.2% for PC), or system losses (20.04% for TF and 19.81% for PC). The PC panels are affected by slightly higher module capture losses due to their higher negative temperature coefficient. It is found, most importantly, that the two PV subsystems have very similar performance behavior when they have similar capacity and operate under the same Shagaya desert environment with the same stringent operational and maintenance strategies. One disadvantage of the TF subsystem, however, is that it requires 18.5% more land area than the PC subsystem to match the installed capacity. The soiling of panels is substantial and requires monthly cleaning with water, which is scarce in a desert environment. A smaller total panel area for a similar power output could constitute a significant economic advantage for the PC technology under such conditions. Highlights: The performance of Shagaya Photovoltaic park after two years' operation is presented. Monitoring soiling is essential at photovoltaic plants located in high soiling areas. Sudden dust storms can cause an instantaneous 30% drop in the photovoltaic power output. Temperature effect on Thin-film and Polycrystalline photovoltaic performance are calculated. Performance ratio, yields, and system losses of different photovoltaic technologies investigated.